Atsar al–Khilaf al–Mu’tabar wal Khilaf Ghairu al–Mu’tabar Fi Fiqhil Islami (Dirasah Tahliliah) - Abdulrahman Zain Ahmed Al-Attas; Noor Naemah Binti Abdul Rahman (State of Islamic Institute Langsa, 2020)
This study aims to analyze several mistakes in the field of contemporary Islam in terms of the concepts that form the basis of several provisions of Islamic law, both in the selection of correct and reasoned concepts and in terms of their influence. The two things are interrelated, where the main reason for this error is the extension of the concept that is less agreed upon and resulting in resistance. Based on the research results, the researcher argued that the right action to overcome the expansion of the concept that was not agreed upon was to limit the meaning so that it could reject the opinion that was not approved. This research also describes the comments for the development of the concept and its provisions, the concept that was not approved, and the lack of consideration in approving the concept which has an impact on the provisions ofIslamic law.